A terpyridine-based test strip for the detection of Hg2+ in various water samples and drinks. Issue 2 (18th December 2018) - Wang, Junjun; Rao, Qingpeng; Wang, Haiyan; Zhang, Qiong; Liu, Gang; Wu, Zhichao; Yu, Jianhua; Zhu, Xiaojiao; Tian, Yupeng; Zhou, Hongping
Abstract : TPI, a novel colorimetric fluorescent compound prepared for test strips, can be used for naked-eye detection of Hg 2+ in tap water samples and drinks conveniently. Abstract : A novel efficient terpyridine-based colorimetric fluorescent compound, TPI, based on the Wittig reaction, was synthesized and impregnated on filter paper into test strips, which could be applied to naked-eye sensing of mercuric ions (Hg 2+ ) in aqueous media through varied emission color from bright blue to yellow.TPI, with nitrogen from pyridine and oxygen from ether, had a high degree of water solubility and a strong coordination ability to Hg 2+ . Importantly, the test strips can be used to qualitatively trace amounts of hazardous Hg 2+ in various water samples and drinks.